“It's Your Problem. Deal with It.” Performers' Experiences of Psychological Challenges in Music - Pecen, Ellis; Collins, David J.; MacNamara, Áine (Frontiers in Psychology, 2018)
Musicians need to deal with a range of challenges during their performance career and in response to these have reported a number of conditions that impact on their performance. Although social support from peers and teachers has been identified as part of the process of dealing with these challenges, little is understood about musicians’ coping methods, beliefs and their attitudes towards support. Therefore, this study aimed to explore a) performers’ previous experiences of psychological challenges, b) the types of support they used and, c) how this might inform future support programs in learning environments. Fifteen interviews were conducted with pre-elite (n=5) transitioning elite (n=3) and established elite performers (n=7) in order to elicit data on psychological challenges, coping, beliefs and preferences for support. Inductive content analysis suggested that elite performers in this sample reported positive health habits, philosophical views of performance, health and life, positive anxiety reappraisal, and use of various psychological strategies, albeit without being explicitly aware of it. The need for various professional skills (e.g., communication, business, self-management and organizational skills) was emphasized by all participants. Transition into conservatoire was marked by severe psychological challenges, disorders and trauma. Primary sources of support included friends, family and self-help literature. Professional help was predominantly sought for physical problems. The impact of teachers was paramount, yet securing good teachers was considered a matter of ‘luck’. The most negative aspects recounted included abusive teachers, unsupportive environments, social comparison, competition and disillusionment after entering the profession. Participants believed that talent could be developed and also valued wellbeing in relation to performance. Positive effects of late specialization on social development and professional skills were also mentioned. Implications and suggestions are discussed.